La Sûreté lyonnaise dans le système policier français (début XIXe-début XXe siècle) - Amos Frappa (Criminocorpus)
In the first half of the nineteen century, “Sûreté” services are created in most of the french cities, as Paris and Lyon. These groups of police whose aim is to arrest criminels, have resemblances such as close links with thieves, a high freedom of action and also the constitution of archives. However, the “Sûreté” services of the two biggest french cities distinguish themselves by their respective organization, as well as by their methods of investigation. It’s in the field of the scientific police that choices diverge from the end of the XIXth century. So, these two models of criminal police spread in France, Europe and also other continents. If Paris obtains an earlier success with Alphonse Bertillon, Lyon also as a sustainable influence with Édmond Locard.